Close association of invading Plasmodium berghei and beta integrin in the Anopheles gambiae midgut. - Mahairaki, V; Lycett, G; Sidén-Kiamos, I; Sinden, R; Louis, C (2005)
We have used confocal microscopy and an antibody against Anopheles gambiae beta integrin to study this protein's distribution in the mosquito midgut and its relationship to invading Plasmodium berghei parasites. An extensive reorganization of integrin is seen to take place in the midgut epithelial cells following the uptake of either non-infected or parasite-infected blood meal, probably reflecting the reshaping of the gut due to the presence of the food bolus and the peritrophic membrane that surrounds it. Furthermore, malaria parasites are coated with beta integrin immediately upon entry into the epithelium, independent of whether they develop intra- or extracellularly. Although this coat is shed a few days after the invasion, beta integrin remains concentrated in the cells surrounding the maturing oocyst for several days. Finally, the antibody detects a structural change in the midgut epithelial cells in the immediate vicinity of the invading ookinete, which is consistent with Plasmodium-induced apoptosis followed by wound healing. This intimate association suggests a specific role of beta integrin in the invasion process.